Platelets modulate cardiac remodeling via the collagen receptor GPVI after acute myocardial infarction - Reusswig, Friedrich; Dille, Matthias; Krüger, E.; Ortscheid, J.; Feige, Tobias; Gorressen, S.; Fischer, J.-W.; Elvers, Margitta (Frontiers in Immunology, 2024)
Platelets play an important role in cardiovascular diseases. After acute myocardial infarction, platelets display enhanced activation and migrate into the infarct zone. Furthermore, platelets trigger acute inflammation and cardiac remodeling leading to alterations in scar formation and cardiac function as observed in thrombocytopenic mice. GPVI is the major collagen receptor in platelets and important for platelet activation and thrombus formation and stability. Antibody induced deletion of GPVI at the platelet surface or treatment of mice with recombinant GPVI-Fc results in reduced inflammation and decreased infarct size in a mouse model of AMI. However, the role of GPVI has not been fully clarified to date. In this exploratory study, we found that GPVI is not involved in the inflammatory response in experimental AMI using GPVI deficient mice that were analyzed in a closed-chest model. However, reduced platelet activation in response to GPVI and PAR4 receptor stimulation resulted in reduced pro-coagulant activity leading to improved cardiac remodeling. In detail, GPVI deficiency in mice led to reduced TGF-beta plasma levels and decreased expression of genes involved in cardiac remodeling such as Col1a1, Col3a1, periostin and Cthrc1 7 days post AMI. Consequently, collagen quality of the scar shifted to more tight and less fine collagen leading to improved scar formation and cardiac function in GPVI deficient mice at 21d post AMI. Taken together, this study suggests GPVI to be a major regulator of platelet-induced cardiac remodeling and supports the potential relevance of GPVI as a potential even therapeutic target to reduce ischemia reperfusion injury and to improve cardiac healing.